الإسلام في إندونيسيا : بين الأصالة والإنحراف - Nasrullah Jasam (Faculty of Islam Nusantara University of Nahdlatul Ulama Indonesia (UNUSIA) Jakarta., 2021)
Some people think that Islam in Indonesia is just a thin skin that covers religious teachings, beliefs and local traditions that exist in the Archipelago. Islam in Indonesia does not really touch the substance, the core of teaching, but merely a cloth from the teachings and traditions that already existed long before in the country. Therefore, Islam has no role in changing the situation of Indonesian society both from a social, economic and political perspective. This paper aims to counter those perception, and argues that Islam in Indonesia in terms of substance has no different from Islam in the Arab world, even though the Archipelago is not the place where the revelation descended, but the preachers who introduced Islam in the Archipelago were mostly preachers from the Arab world. Those preachers (da'i) with their intelligence, were able to spread Islam throughout the Archipelago in a relatively short time, without resistance from local religious adherents. This success could not be separated from the da'wah strategy of the da'i, namely by making local traditions as media for da'wah. So that the population of the Archipelago voluntarily embraced Islam. Substantially, there are no different between Islam in Indonesia and Islam in the Arab lands. The only distinctiveness lays on the da'wah strategy, namely by accomodating local traditions.